KAJIAN FINANSIAL PENGEMBANGAN BIODIESEL KEMIRI SUNAN (Reutealis trisperma (Blanco) Airy Shaw) PADA LAHAN TERSEDIA DI JAWA BARAT - Wening Sri Wulandari; Dudung Darusman; Cecep Kusmana; Widiatmaka Widiatmaka (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2015)
One of potential vegetable materials in Indonesia as a source of biodiesel is kemiri sunan (Reutealis trisperma (Blanco) Airy Shaw). This study aims to analyze: financial feasibility of plantation; financial feasibility of biodiesel processing, and the development of business unit. The research results show that kemiri sunan plantation is feasible on the area of 60 ha, a business period of 50 years. Feasibility values without loan are: NPV IDR 1,101,007,645; IRR 13.52%; BCR 1.36; PBP 14.68 years, feasibility values with loan are: NPV IDR 160,351,357; IRR 13.52%; BCR 1.08; PBP 22.55 years, sensitive to the decrease of selling price of dry seeds and productivity of the trees. The biodiesel processing business is feasible at the business period of 15 years, the production capacity of 202.75 Kl/year. Feasibility values without loan are: NPVIDR 512,549,740; IRR 27.27%; BCR 1.04; PBP 4.32 years, feasibility values with loan are: NPV IDR 303,310,940; IRR 27.27%; BCR 1.03; PBP 4.94 years, sensitive to the rising costs of materials and a decrease in the selling price. If all available lands were cultivated, it will generate 2,365 business units and to produce biodiesel that meets 16.68% of the needs of West Java diesel oil.